1972
DOI: 10.3181/00379727-139-36116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pentobarbital on Plasma Glucose and Free Fatty Acids in the Rat

Abstract: Animals are frequently anesthetized prior to blood collection or tissue sampling to expedite handling. Nembutal,2 a drug containing sodium pentobarbital as the active anesthetic agent, is popular for such purposes.In this laboratory, it became necessary to institute special bleeding procedures. Rats were anesthetized with Nembutal, the abdominal cavity was opened, and blood was removed by needle puncture of the aorta. By happenstance, it was found that plasma free fatty acids were lower and plasma glucose high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Previous studies have indicated that most anesthetic agents induced hyperglycemia except sodium pentobarbital [40][41][42] . However, other previous studies reported hyperglycemia as a result of pentobarbital overdose www.nature.com/scientificreports www.nature.com/scientificreports/ (100 and 150 mg/kg) in agreement with the present study 43,44 . The increased glucose plasma levels recorded in the present study may be due to induction of hepatic insulin resistance which in turn causes gluconeogenesis and hyperglycemia 45,46 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have indicated that most anesthetic agents induced hyperglycemia except sodium pentobarbital [40][41][42] . However, other previous studies reported hyperglycemia as a result of pentobarbital overdose www.nature.com/scientificreports www.nature.com/scientificreports/ (100 and 150 mg/kg) in agreement with the present study 43,44 . The increased glucose plasma levels recorded in the present study may be due to induction of hepatic insulin resistance which in turn causes gluconeogenesis and hyperglycemia 45,46 .…”
Section: Discussionsupporting
confidence: 93%
“…Glycemia did not differ significantly among the groups, but it tended to be lower in the CR compared with the AL-fed group. Blood was sampled by cardiac puncture after anesthesia with pentobarbital sodium, which can increase circulating glucose in rats (16). Thus absolute glucose values should be interpreted with caution, but the relative difference (8%) between AL-fed and CR rats compares with the relative reduction (4-10%) previously reported for arterial blood from unanesthetized CR vs. AL-fed rats (10,37).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, which have been most extensively studied, there are no metabolic data from conception to term. In addition, most of the data in rats have been obtained over the latter half of gestation using a variety of techniques [by decapitation (9,27); under anesthesia (14,20,33); in awake animals (39); and most recently, in chronically chatheterized animals (lo)]. These studies have produced quite variable results.…”
Section: Discussionmentioning
confidence: 99%